Parallelizing Satz Using Dynamic Workload Balancing - Jurkowiak, Bernard; Li, Chu Min; Utard, Gil (Electronic notes in discrete mathematics, 2001)
We presents the parallelization of Satz using work stealing for workload balancing, based on the master/slave communication model. We define a simple way to evaluate the workload of every busy slave. The master then steals the first remaining subtree of the most loaded slave for an idle slave. Special attention is paid to prevent pingpong phenomenon. Our approach easily supports fault tolerance computing and accumulation of intermediate results over time. Encouraging experimental results are presented. We thank Dominique Lazure for material help and Laure Devendeville for fruitful discussions. This work is partially supported by grant of “pô le de modélisation de la région de Picardie”.